1981
DOI: 10.1159/000275541
|View full text |Cite
|
Sign up to set email alerts
|

Otological Aspects of the Earpit-Deafness Syndrome

Abstract: The results of a systematic study of the otological aspects in 13 cases of earpit-deafness syndrome are reported. The audiometric, radiological and vestibular findings as well as the results of exploratory tympanotomies with and without stapedectomies are discussed together with the results reported in the literature. A convincing explanation of the poor results of exploratory tympanotomies in cases with mixed hearing loss is not furnished. If the hearing loss is confined to conduction and ankylosis of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…This study clearly demonstrated the limitation of middle ear surgeries for hearing improvement in patients with BOR/BO syndrome consistent with previous reports [19]. The failure may be explained by several reasons.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study clearly demonstrated the limitation of middle ear surgeries for hearing improvement in patients with BOR/BO syndrome consistent with previous reports [19]. The failure may be explained by several reasons.…”
Section: Discussionsupporting
confidence: 91%
“…Cremers et al [19] have reported that the hearing loss in BOR/BO syndrome was stable without progression or fluctuation. However, half of the patients included in this study demonstrated various degrees of progressive hearing loss, and also sudden aggravation of hearing was demonstrated in one patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, families having either branchial and hearing impairment (BO) or branchial and renal defect (BR) are not necessarily due to the same gene affecting three organs, as is true for BOR. Cremers et al, 1981;Melnick et al, 1976;Fraser et al, 1978 …”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION Preauricular sinuses, pinna dysplasia, and deafness can be expressions of branchiogenic disorders as observed in Treacher Collins syndrome, the BOR syndrome, and the hemifacial microsomia syndrome. [5][6][7] But these features can exist as separate entities as well.…”
Section: Resultsmentioning
confidence: 99%